Tindak Tutur Lokusi, Ilokusi, dan Perlokusi dalam Konten Youtube PWK Bersama Dr. Tirta (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
Podcasts as digital communication media have continued to grow and have become an important platform for delivering ideas, opinions, and public education. This study aims to analyze locutionary, illocutionary, and perlocutionary speech acts in the YouTube content Podcast Warung Kopi (PWK) entitled “Mental Dr. Tirta Turun, Gara-Gara Video Marah-Marah Dilihat dan Ditiru Sama Anaknya.” This research employs a descriptive qualitative method using listening and note-taking techniques to examine the utterances produced by the host and the guest speaker. The data consist of transcribed conversations that are classified based on Austin’s speech act theory. The findings reveal 17 speech act data, consisting of 4 locutionary acts, 9 illocutionary acts including assertive, directive, expressive, and commissive types, and 4 perlocutionary acts. These results indicate that podcasts function not only as entertainment and information media but also as effective tools in influencing listeners’ attitudes, raising awareness, and shaping behavioral responses, particularly in relation to health and social issues.